Docking de compostos da família das ariloxazinas em enzimas relacionadas com a malária - Corrêa, Denis da Silva (Universidade Federal de São Carlos, 2010)
Malaria disease, caused mainly by Plasmodium falciparum parasite, afflicts about 500 million people and causes nearly one million deaths every year. For the development of new drugs against this disease, one possible approach is to identify an enzyme that plays a key role in P. falciparum development and presents significantly different properties from the corresponding human one. These differences can be exploited in the design of specific inhibitors of the parasite s protein, thus, three different enzymes were selected as possible targets. As there are evidences suggesting that increasing oxidative stress can effectively inhibit the growth of the malarial parasite the enzyme Glutathione Reductase of P. falciparum (PfGR), responsible for the parasite s antioxidant defense, has become a potential target for the design and development of inhibitors. The second target was the P. falciparum Dihydrofolate Reductase-Thymidylate Synthase (PfDHFR-TS), and in this case blocking its action stops the dTMP production and DNA synthesis in the parasite. The third chosen target was the P. falciparum Lactate Dehydrogenase (PfLDH), whose inhibition interrupts the ATP formation and thus causing the death of the parasite. So that a family of arilloxazines compounds, together with chloroquine and methylene blue, were studied by means of docking simulations in the binding sites of these enzymes and also in the corresponding human enzymes for comparison. The three-dimensional structures of the enzymes and of chloroquine and methylene blue were obtained from the Protein Data Bank (PDB). The structures of the arilloxazines compounds, in turn, were obtained by molecular modeling with HyperChem 6.01 and MOPAC2009 programs, using as starting models similar crystallographic structures deposited in the Cambridge Structural Database. Docking simulations were performed using GOLD 4.0.1. The docking results showed that the enzymes PfGR and PfDHFR-TS are not the preferential targets of chloroquine. For the methylene blue it was possible to elucidate its binding mode in hGR and PfGR. Regarding the arilloxazines it was possible to show that they present their higher affinity for hGR, followed by PfGR, hDHFR, PfDHFR-TS, PfLDH and hLDH. In the case of GRs, the interface site was the preferred binding site. The results suggest that if arilloxazines compounds with higher affinity for PfGR are desirable then a pentafluorophenyl should be attached at the N10 position, as in the 2e compound. When searching for arilloxazines with higher affinity for PfLDH, it seems to be desirable a carboxymethyl group at the N3 position (as in 5b) and a pentafluorophenyl group at N10 (as in 2e). Finally, the results suggest that in general the studied arilloxazines probably will present a higher affinity for hDHFR than PfDHFR-TS. All these results are an important starting point for the design of new arilloxazines ligands so that they can be used as lead compounds in the search for new drugs against malaria.
Docking of arilloxazines in enzymes related to malaria
Keywords: Biotecnologia; Glutationa redutase; Bioinformática; Biologia molecular; Ariloxazinas; Plasmodium falciparum; Malária; Docking; Arilloxazines; Glutathione reductase; Dihydrofolate Reductase-Thymidylate Synthase; Lactate dehydrogenase; Plasmodium falciparum; Malaria; OUTROS